Implications for concussion assessments and return-to-play standards in intercollegiate football: How are the risks managed? - John J. Miller; John T. Wendt; Nick Potter (Journal of Applied Sports Management, 2011)
The lack of understanding regarding the symptoms and effects of concussions by athletes and coaches can generate pressure on both the team physicians to diagnose concussions as well as the sport administrators who need to be aware what concussion protocols are being followed. The significance of appropriate diagnosis of a concussion and the returnto-play protocols may be complicated by the number of guidelines available as well as the reliance on the athlete to self-report the symptoms of a concussion. While the grading guidelines have advanced the use of uniform terminology and increased awareness of concussion signs and symptoms, the lack of scientific method in creating the concussion management guidelines called their effectiveness into question. A total of 65 head football athletic trainers were surveyed to determine how medical personnel at selected universities managed the risk of concussions in intercollegiate football. The results indicated that nearly 70% of the respondents indicated that between five to eight football players on their respective teams incurred a concussion during the season. However, no dominant guidelines for assessing a concussion were revealed as none of the guidelines were employed by more than 29% of the population. Finally, 50% did not believe that the same guidelines should be used for an initial concussion assessments or subsequent concussions. Because no two people can be diagnosed in exactly the same way, guidelines may inhibit proper treatment. However, should an error in judgment occur, litigation against the physician, the athletic administrator, and the university may result.
Keywords: Concussion; Guidelines